Pelatihan Media Pembelajaran Interaktif Berbasis Wordwall bagi Guru-Guru SMA Negeri 2 Campalagian - Ummu Kalsum; Musdar M; Andi Rosman N; Nur Fadhilah Umar (JKM: Jurnal Kemitraan Masyarakat, 2024)
SMAN 2 Campalagian is one of the educational institutions that continuously strives to improve its learning quality. Currently, the use of technology has not been optimized in SMAN 2 Campalagian due to limited resources and knowledge about interactive learning media such as Wordwall that is effective for teachers. This community service activity (PKM) aims to introduce and train the use of Wordwall as a learning media at SMA Negeri 2 Campalagian. Through this activity, it is hoped that teachers at SMA Negeri 2 Campalagian can improve their skills in using learning technology, so as to create a more interesting and meaningful learning experience for students.  The implementation method used in this PKM activity is in the form of training and demonstration of making Wordwall-based interactive media.  The results of this service are that the training participants have been able to increase their knowledge and skills in making Wordwall-based interactive learning media. Participants have been able to use Wordwall with a percentage of 85% from previously only 30%. In addition, the use of content and features from Wordwall also increased by 90% from the initial 35%. Finally, the ability to design attractive media also showed that the partners' skills increased by 90%.